Reconfigurable bandstop to allpass filter using defected ground structure in K-band for millimeter-wave communications - Adib Othman; Noor Azwan Shairi; Huda A. Majid; Zahriladha Zakaria; Imran Mohd Ibrahim; Mohd Haizal Jamaluddin; Anwar Faizd Osman (Institute of Advanced Engineering and Science, 2022)
In this paper, a reconfigurable bandstop to allpass filters using Defected Ground Structure (DGS) in K-Band for millimeter-wave communications is proposed. Mathematical analysis of the DGS is discussed in this paper for the bandstop and allpass responses. The reconfigurable filter is performed by using an ideal switch with open circuit and short circuit conditions on DGS at several locations. Hence, two filter designs with different DGS are investigated for their performance in both simulation and measurement. As a result, the ideal switch at location S3 gives the best performance for both DGSs with a narrowband bandstop response and a wideband allpass response with insertion loss of less than 1 dB and return loss of more than 10 dB at the 26 GHz band. Hence, the proposed reconfigurable filter is suitable for millimeter-wave front-end communications.